2007
DOI: 10.1105/tpc.106.047159
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis JAGGED LATERAL ORGANSIs Expressed in Boundaries and CoordinatesKNOXandPINActivity

Abstract: Plant lateral organs are initiated as small protrusions on the flanks of shoot apical meristems. Organ primordia are separated from the remainder of the meristem by distinct cell types that create a morphological boundary. The Arabidopsis thaliana gain-of-function mutant jagged lateral organs-D (jlo-D) develops strongly lobed leaves, indicative of KNOX gene misexpression, and the shoot apical meristem arrests organ initiation prematurely, terminating in a pin-like structure. The JLO gene, a member of the LATER… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
141
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(146 citation statements)
references
References 54 publications
5
141
0
Order By: Relevance
“…However, several loss-of-function mutants of rice and maize LBD genes have been reported to evidence clear phenotypes (Inukai et al, 2005;Liu et al, 2005;Bortiri et al, 2006;Evans, 2007;Taramino et al, 2007). The ectopic expression of several LBD genes, as wild type or as proteins fused to a transcriptional repression domain, yielded morphological phenotypes, provid- ing clues to the biological functions of these LBD genes (Shuai et al, 2002;Chalfun-Junior et al, 2005;Borghi et al, 2007;Okushima et al, 2007). For example, the overexpression of LBD16 or LBD29 induced lateral root formation in the absence of ARF7 and ARF19, and the dominant repression of LBD16 activity inhibited lateral root formation; these findings suggest that these LBDs function downstream of ARF7-and ARF19-dependent auxin signaling in lateral root formation (Okushima et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several loss-of-function mutants of rice and maize LBD genes have been reported to evidence clear phenotypes (Inukai et al, 2005;Liu et al, 2005;Bortiri et al, 2006;Evans, 2007;Taramino et al, 2007). The ectopic expression of several LBD genes, as wild type or as proteins fused to a transcriptional repression domain, yielded morphological phenotypes, provid- ing clues to the biological functions of these LBD genes (Shuai et al, 2002;Chalfun-Junior et al, 2005;Borghi et al, 2007;Okushima et al, 2007). For example, the overexpression of LBD16 or LBD29 induced lateral root formation in the absence of ARF7 and ARF19, and the dominant repression of LBD16 activity inhibited lateral root formation; these findings suggest that these LBDs function downstream of ARF7-and ARF19-dependent auxin signaling in lateral root formation (Okushima et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Although the lbd36 loss-of-function mutants did not show morphological phenotypes, the analysis of lbd36 as2 double mutants showed that these two members act redundantly to control cell fate determination in the petals. Another Arabidopsis gain-of-function mutant, jagged lateral organs-D (jlo-D), generates strongly lobed leaves and the shoot apical meristem prematurely arrests organ initiation, terminating in a pin-like structure (Borghi et al, 2007). During embryogenesis, JLO (=LBD30/ASL19) is necessary for the initiation of cotyledons and development beyond the globular stage.…”
mentioning
confidence: 99%
“…LOB was initially identified from an enhancer trap screen for genes expressed at the adaxial base of initiating lateral organs and other family members identified based on conservation of the so-called N-terminal LOB domain (Shuai et al, 2002). For most LBD family members the function is not known, but for some, roles have been defined in organ development, anthocyanin, and nitrogen metabolism, as well as in responses to phytohormones such as cytokinin, auxin, and gibberellin (Borghi et al, 2007;Bureau et al, 2010;Majer and Hochholdinger, 2011;Feng et al, 2012). To our knowledge, our findings represent the first functional characterization of LBD20 and the first demonstration of a role for any LBD family member in plant-pathogen interactions.…”
Section: Discussionmentioning
confidence: 99%
“…A role for combined regulation of KNOX and auxin activities in boundary delimitation was also suggested by analysis of the boundary-expressed LOB domain gene JAGGED LATERAL ORGANS (JLO), which is sufficient to activate STM and BP expression and repress PIN auxin efflux transporters (Fig. 4) (Borghi et al, 2007).…”
Section: A Cmentioning
confidence: 99%